Mengungkap Keberhasilan Mempertahankan Usaha Toko Roti The Vos Bakery Di Tusam Banyumanik - Kharisma, Dina; Hidayah, Nining (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to find out what factors make The Vos Bakery survive amidst such tight competition. This research uses qualitative research methods and the research design used is a case study. In determining informants, researchers used a purposive sampling method or determining informants with certain considerations. The selected informants were the owners, employees and customers of The Vos Bakery using data collection methods using interviews, observation and documentation. The data analysis technique was carried out using triangulation techniques. The research results show the factors that make The Vos Backry bakery business survive amidst intense competition with the principles of being confident in facing competition, daring to take risks, working hard and patiently, strategic location, maintaining product quality, and affordable prices